Monitoring HIV testing in diverse healthcare settings: results from a sentinel surveillance pilot study. Issue 5 (28th April 2010) - Tweed, Emily; Hale, Antony; Hurrelle, Martin; Smith, Ruth; Delpech, Valerie; Ruf, Murad; Klapper, Paul; Ramsay, Mary; Brant, Lisa
Abstract : Objectives: To assess the feasibility and utility of sentinel laboratory surveillance of HIV testing as a tool for understanding patterns and trends in HIV testing in a range of healthcare services. Methods: Data on all anti-HIV antibody tests carried out by the Leeds Teaching Hospital Trust laboratory over a 12-month period were collated and analysed by demographic information and place of test. Individuals who tested positive were matched to the national database of HIV diagnoses to identify the proportion newly diagnosed with HIV. Results: 41 013 individuals over 1 year of age were tested at least once for HIV during the study period, of whom 0.8% (n=312) were positive. The majority of individuals (77%) were tested in a genitourinary medicine (GUM) clinic or as part of antenatal care, while routine testing of people undergoing haemodialysis, fertility treatment or occupational health screening accounted for a further 13% of those tested. Few individuals (<4%) were tested in general practice. Of the 312 people testing positive, 286 could be matched to the HIV national database and 173/286 (60%) were identified as newly diagnosed. Conclusions: Little HIV testing is currently performed outside GUM and antenatal settings. Monitoring of HIV testing is essential given new guidelines recommending the expansion of testing in a wide range of settings. Sentinel laboratory surveillance can provide useful demographic data on people tested for HIV and can assess trends in testing over time. Data on HIV testing could be incorporated into existing hepatitis sentinel surveillance, allowing rapid scale-up of this surveillance scheme with minimal effort.